Initial experiences of extended pelvis lymphadenectomy in radica cystectomy patients for treatment invasive bladder cancer - Tung, Hoang Van; Vinh, Le Luong; Khanh, Tran Ngoc; Liem, Ngo Thanh; Thanh, Tran Van; Khanh, Le Dinh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.